2022
DOI: 10.3390/electronics11091330
|View full text |Cite
|
Sign up to set email alerts
|

Super-Twisting Sliding Mode Control for Differential Steering Systems in Vehicular Yaw Tracking Motion

Abstract: This paper deals with the modelling and control of differential steering for vehicular motions with the help of Sliding Mode Control (SMC) with a Super-Twisting Algorithm (STA). A single-track mechanical model of the vehicular dynamics is proposed and validated by simulations. A control strategy based on the STA is proposed for the yaw dynamics to improve travel comfort and the stability of the vehicular motion. The desired yaw trajectory is given and the equivalent and corrective control parts of the STA are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Although the sliding mode [9] regulator can dispose of the relatively sophisticated control system to ensure its good robustness and speed of response, the system will buffet during the process. This thesis proposes an integral sliding mode control manner to ameliorate the approach law to solve this problem.…”
Section: Improve the Integral Sliding Mode Controllermentioning
confidence: 99%
“…Although the sliding mode [9] regulator can dispose of the relatively sophisticated control system to ensure its good robustness and speed of response, the system will buffet during the process. This thesis proposes an integral sliding mode control manner to ameliorate the approach law to solve this problem.…”
Section: Improve the Integral Sliding Mode Controllermentioning
confidence: 99%
“…From Figure 5, it can be observed that R À W 2 represents the radius of curvature of the trajectory describing the left wheel, while R + W 2 represents the radius of curvature of the trajectory describing the right wheel. In this case, the rotation angle of the vehicle when turning left and right is expressed by equations ( 28)- (29).…”
Section: Computational Model For Wall Climbing Robot Carmentioning
confidence: 99%
“…[25][26][27] This technology is highly beneficial in solving manufacturing issues by utilizing lightweight materials while ensuring durability. 28,29 The principle of 3D printing involves creating the object by layering materials on top of each other, with each layer being fused together through additives, heat, or light. [30][31][32][33] The printing material is responsible for constructing the product, and as the components are fabricated using 3D printing, the mechanical properties of the material are closely monitored and appropriately calculated.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the optimization schemes of active and semi-active suspension control strategies are weight coefficient optimization for a single working condition. In the actual driving process of vehicles, road conditions are complex and changeable, and the change in vehicle conditions will affect the actual control effect [ 30 , 31 ]. Road working condition parameters can be obtained to optimize active suspension control and obtain better control effects under different road conditions and speeds, which can better improve vehicle comfort and ride comfort [ 5 , 32 ].…”
Section: Introductionmentioning
confidence: 99%